The development of an instrument to measure the grit of junior high school students using the rasch analysis model - Jannah, Raudha Nur Hidayah Al; LN, Syamsu Yusuf; Setiawati, Setiawati Setiawati (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to obtain a valid and reliable Student Grit Scale and to analyze the feasibility of a measurement instrument using the Rasch Model. This study employed a quantitative research method with a descriptive approach and involved 75 junior high school students. The grit scale developed by Datu, called the Triarchic Model of Grit (TMG), was used in this study. The results of the reliability test showed that Cronbach's Alpha was greater than 0.60 (), indicating that the measurement instrument was reliable. The unidimensional analysis showed that the instrument was feasible because the variance observed in the contrast of 1 to 5 residues contained only values above 15%. Thus, the entire construct of the grit has measured one appropriate variable. This study provides recommendations for the development of a grit measurement instrument to investigate he balance between the topics contained in the questions and the level of ability of students as respondents.